2020
DOI: 10.17749/2313-7347.141
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory monitoring of COVID-19 patients and importance of coagulopathy markers

Abstract: The pandemic of a new coronavirus infection COVID-19 has become a real challenge to humanity and the medical community and has raised a number of medical and social issues. From the currently available information on clinical cases of COVID-19, it follows that COVID-19 patients in critical condition have a clinical picture of disseminated intravascular coagulation (DIC), septic shock with the development of multiple organ failure, which justifies the anticoagulant therapy use in patients with COVID-19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 47 publications
0
3
0
5
Order By: Relevance
“…Весь прошлый год прошел под знаком беспрецедентной пандемии новой коронавирусной инфекции, поставившей множество вопросов, начиная от диагностики и лечения и завершая управленческими решениями с целью снижения пиковой нагрузки на систему здравоохранения [1][2][3]. Спустя практически год после начала пандемии COVID-19 стало известно, что наибольшую опасность представляют беременные группы риска, у которых имеется противовоспалительный статус и хронические нарушения гемостаза.…”
Section: • том 15 • №unclassified
“…Весь прошлый год прошел под знаком беспрецедентной пандемии новой коронавирусной инфекции, поставившей множество вопросов, начиная от диагностики и лечения и завершая управленческими решениями с целью снижения пиковой нагрузки на систему здравоохранения [1][2][3]. Спустя практически год после начала пандемии COVID-19 стало известно, что наибольшую опасность представляют беременные группы риска, у которых имеется противовоспалительный статус и хронические нарушения гемостаза.…”
Section: • том 15 • №unclassified
“…In patients with COVID-19, thrombocytopenia mechanism is probably multifactorial. It was suggested that a combination of the viral infection and an artificial ventilation leads to endothelial damage, triggering platelet activation, aggregation, and thrombosis in the lungs, in which significant platelet consumption occurs [13]. Moreover, since the lung can be a site of release of platelets from mature megakaryocytes, severe pneumonia can lead to impaired platelet defragmentation.…”
Section: Possible Mechanisms Of Pathogenesis Of Vascular Complicationmentioning
confidence: 99%
“…Одним из маркеров нарастания тяжести течения COVID-19 является ферритин. Функция ферритина заключается в связывании и переносе ионов железа, а также участии в иммунных и воспалительных реакциях [17]. Исследования показали, что воспалительный ответ на вирусную инфекцию (IL-18/ферритин) выступает специфическим плазменным иммунным биомаркером.…”
Section: патогенез тромботических осложнений у пациентов с Covid-19unclassified
“…Резка мультимеров происходит при участии фермента металлопротеиназы ADAMTS-13 (a Disintegrin and Metalloprotease with Thrombospondin Type 1 Motif 13) после связывания в области А2 домена ФВ. Этот процесс активируют тромбоциты и фактор свертывания VIII [17]. ADAMTS-13 представляет собой протеазу из семейства металлопротеиназ.…”
Section: патогенез тромботических осложнений у пациентов с Covid-19unclassified